2020
DOI: 10.3390/biom10040606
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Spectroscopy Study of the Secondary Structure Changes in Human Serum Albumin and Trypsin under Neutral Salts

Abstract: The effect of neutral salts on protein conformation was first analyzed by Hofmeister in 1888, however, even today this phenomenon is not completely understood. To clarify this effect, we studied changes in the secondary structure of two proteins: human serum albumin with predominantly α-helical structure and porcine pancreas β-trypsin with the typical β-structural arrangement in aqueous solutions of neutral salts (KSCN, KCl, (NH4)2SO4). The changes in the secondary structure were studied at 23 °C and 80 °C by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 49 publications
4
20
0
Order By: Relevance
“…On the other hand, proteins with a helical bundle structure require a higher threshold of ionic strength (typically 100−500 mM) to have a defined structure and they tend to aggregate due to unstable structure when ionic strength is low. 25,27,29 Once the ionic strength is above the threshold, the protein has increased stability, as we have observed for SUP at 300 mM NaCl concentration. Due to these to two competing factors, we have observed a significant aggregation at a salt concentration of 100 mM when the salt-out effect is dominated, but have seen a decreased aggregation when salt concentration is further increased to 300 mM under which the helix-bund structure stabilizes the protein.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, proteins with a helical bundle structure require a higher threshold of ionic strength (typically 100−500 mM) to have a defined structure and they tend to aggregate due to unstable structure when ionic strength is low. 25,27,29 Once the ionic strength is above the threshold, the protein has increased stability, as we have observed for SUP at 300 mM NaCl concentration. Due to these to two competing factors, we have observed a significant aggregation at a salt concentration of 100 mM when the salt-out effect is dominated, but have seen a decreased aggregation when salt concentration is further increased to 300 mM under which the helix-bund structure stabilizes the protein.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…Transformed cells were grown in terrific broth (TB) 13 (Ampicillin 100 μg/mL) at 37 °C, 250 rpm for 4 h, protein expression was induced by adding 1 mM isopropyl β-D-1thiogalactopyranoside (IPTG) and incubated at 20 °C, 250 rpm for 16 h. Harvested cells by centrifugation at 10,000 rpm, 10 min at 4 °C were resuspended in lysis buffer (10 mM Tris-HCl pH 7.5, 500 mM NaCl, 1 mM PMSF, 2% Triton-X 100) and lysed using a probe sonicator (QsonicaQ125) for 5 min (30 s on 30 s off, amplitude 90%). Soluble proteins were recovered by centrifugation at 10,000 rpm, 10 min at 4 °C, and purified using metal affinity chromatography (GE Healthcare) by step elution (10,25,50, and 100% of Elution buffer) from 0 to 500 mM imidazole in 10 mM Tris-HCl buffer pH 7.4, 500 mM NaCl. After purification, the engineered proteins were desalted to 10 mM N-(2-hydroxyethyl)piperazine-N′-ethanesulfonic acid (HEPES) pH 7.4 using a G25 Sephadex desalting column (GE Healthcare).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The proteins in the blood plasma, as well as the amino group in the TRIS contained in the SBF, were capable of spectrally interfering with the amide I band. Human serum albumin, the most abundant protein in plasma, embodies predominantly an α-helical structure and, upon interaction with neutral salts, may lead to the formation of intermolecular β-sheets [ 34 ]. Both these secondary structures are able to influence the deconvoluted band areas in amide I.…”
Section: Resultsmentioning
confidence: 99%
“…While they can be considered as eco-friendly solvents, many proteins are inherently inactive in ILs, requiring the addition of water for activity recovery. This suggests ILs could affect the internal water shell [61,62].…”
Section: Salt Effectmentioning
confidence: 99%
“…Changes in the secondary structure of two proteins with helical and beta structural arrangement, respectively, were followed by Fourier Transform Infra-Red spectroscopy (FTIR) in the presence of various salts. It was shown that the stabilization effect of the salt follows the Hofmeister series of ions, although some exceptions were observed with formation of intermolecular β-sheets typical of amorphous aggregates [62]. Glucose oxidase (GOx) stability was studied using microcalorimetry in the presence of various salts [63].…”
Section: Salt Effectmentioning
confidence: 99%